Mouse models address key concerns regarding autophagy inhibition in cancer therapy - Amaravadi, Ravi (2014)
With multiple clinical trials underway targeting autophagy against cancer, Yang et al. (1) and Karsli-Uzunbas et al. (2) address important concerns regarding autophagy inhibition in cancer patients using genetically engineered mouse models (GEMMs) that more accurately represent the tumor biology found in human pancreatic and lung cancer patients.